Bending-shear interaction buckling of stainless steel plate girders: Numerical investigation and design method. (January 2023) - Chen, Xiaowan; Yuan, Huanxin; Real, Esther
Abstract: A comprehensive numerical investigation of transversely stiffened stainless steel plate girders under combined bending and shear was carried out in this paper. By using the finite element (FE) software package ABAQUS, numerical models with incorporation of material nonlinearity, initial geometric imperfections and welding residual stresses were developed, and were used to replicate previously obtained test results. The validated numerical models were employed to perform parametric studies to generate structural data points for stainless steel plate girders over a broad range of cross-sectional properties, involving various combinations of bending moment and shear force. The summarised test and FE results were compared with the predicted strengths determined according to European code EN 1993-1-5 and proposals of Jáger et al., Chinese code GB 50017-2017, and American specification ANSI/AISC 370-21, highlighting that the applicability of existing design methods in predicting the ultimate resistances of stainless steel plate girders under combined bending moment and shear force was limited. By referring to the design methods in GB 50017-2017 and ANSI/AISC 370-21, two separate design recommendations were proposed, respectively. Further reliability analyses were performed to verify the applicability of the abovementioned design methods.